Modified process of image reproduction and amplification for measurement of area by planimetry: Application in plain wounds produced in dogs treated by occlusive skin frog dressings - Falcão, Suyiene Cordeiro; Coelho, Antonio Roberto de Barros; Almeida, Edvaldo Lopes de; Galdino, Carlos Alberto Pessoa de Mello (Brazilian Journal of Veterinary Research and Animal Science, 2001)
Digital image analysis and planimetry are important tools for evaluation of plain wound areas submitted to local treatment. In the proposed process, perimeters of wound areas were obtained in loco by tracing over transparent sheet and further reproduced and amplified by laser copier, precluding the use of photography and developing. The contraction and granulation areas were then measured by planimeter. Epitelization area were determined by difference between the above mentioned areas. Data from measurements and determinations of areas were further transformed in cumulative Percentage of Wound Contraction (PWC), Wound Epitelization (PWE) and Wound Healing (PWH). The proposed process was tested in square shaped lesions (400 mm²), produced in both right and left thoraco-dorsal surfaces of dogs. Seventeen lesion localized in the right thoraco-dorsal region were treated by Rana catesbeiana skin, previous preserved by hypothermia (Test Group). Another 17 lesions in left thoraco-dorsal surface were treated by moistened gauze (Control Group). PWC, PWE and PWH were evaluated at the 7th, 14th, 21th and 28th POD. Macro and microscopic studies showed skin frog destruction, suggestive of rejection phenomenon. It follows that: 1. Changes in reproducing image process permitted to save costs. The reading error of planimeter was ± 0.5%; 2. PWC, PWE and PWH showed non significant differences between Groups. Such equivalence was attributed to destruction of frog skin, suggestive of rejection process.